TECHNOLOGICAL PROGRESS AND ITS ROLE IN DIVERSIFYING ENERGY SOURCES (World Bulletin of Management and Law, 2022)
This research consists of three topics, the researcher tries to clarify in the first research the concept of energy sources of both renewable and nonrenewable types with a simple explanation of each, nd completes in the second topic to clarify the technology used recently to obtain clean energy and less impact on the environment, The researcher returns in the third topic to explain the impact of this technology and technical development on the diversity and multiplicity of sources that provide us with energy.
Keywords: Boxer; Psychological And Volitional Training; Training Process; Coach